Digital Marketing, Social Media And Influencers On The Recognition of Airline Brands - Sari, Mustika; Firdaus, Muhammad Iqbal; Irfansyah, Muhammad Dafa (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2024)
In the digital era, digital marketing, social media, and influencers play a crucial role in introducing brands to public. Internet technology allows for fast and accurate information dissemination, making it an effective and efficient tool for increasing brand awareness. The rapid growth of internet and social media usage in Indonesia has created opportunities for companies to leverage these platforms. The company, a private aviation company, aims to maintain its position as the preferred choice for customers by enhancing brand awareness. By utilizing digital marketing, social media, and influencers with the right strategies, the company can enhance its brand awareness. The research aims to analyze the influence of digital marketing, social media, and influencers on brand awareness. The study used a Quantitative research method with data analysis technique using Structural Equation Modeling based on partial least squares, a statistical method that examine the complex relationships betweaen variables. The research shows that digital marketing, social media, and influencers have a significant and favorable impact on brand awareness. The study emphasizes the relevance of these digital tools in today's marketing landscape and gives practical information for companies to develop their strategies, ensuring the company's long-term success and market exposure.